2015
DOI: 10.1007/s11596-015-1407-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of high alert medication knowledge of medical staff in Tianjin: A convenient sampling survey in China

Abstract: The current situation of medical staff's awareness about high alert medication was investigated in order to promote safe medication and standardized management of the high alert medication in China. Twenty questions were designed concerning elementary knowledge of high alert medications, storage management, medication issues and risks. In order to understand the knowledge level and education status of high alert medication, a convenient survey was conducted among 300 medical staffs in Tianjin. Medical staff's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 25 publications
0
27
1
2
Order By: Relevance
“…Estudos de avaliação de conhecimento sobre MPP entre membros de equipes médicas, farmacêutica e de enfermagem são escassos, 17,18 porém, estratégicos para mapear lacunas de segurança a serem preenchidas no processo assistencial. 5,8,[10][11][12][13]19,20 O perfil profissional dos participantes revelou a presença marcante de mulheres e a faixa etária prevalente de 31 a 39 anos, sendo semelhante ao identificado em diferentes estudos de perfil profissional no Brasil.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Estudos de avaliação de conhecimento sobre MPP entre membros de equipes médicas, farmacêutica e de enfermagem são escassos, 17,18 porém, estratégicos para mapear lacunas de segurança a serem preenchidas no processo assistencial. 5,8,[10][11][12][13]19,20 O perfil profissional dos participantes revelou a presença marcante de mulheres e a faixa etária prevalente de 31 a 39 anos, sendo semelhante ao identificado em diferentes estudos de perfil profissional no Brasil.…”
Section: Discussionunclassified
“…17 Diferenças no conhecimento entre os profissionais de saúde sobre MPP foram também identificadas em estudo realizado por Engels e Ciarkowski 17 e Tang e colaboradores. 18 Para Engels e Ciarkowski, a educação profissional sobre o tema, contribui para que os profissionais aceitem e reconheçam seu papel e responsabilidades no processo de utilização de MPP; e para eliminar lacunas nas estratégias de redução do risco de utilização destes medicamentos, e que o conhecimento sobre MPP deve ser abordado na formação profissional e reforçado no trabalho. 12,17 O desconhecimento dos residentes médicos e multiprofissionais sobre os MPP e o ciclo de utilização dos mesmos no hospital é, possivelmente, reflexo de lacuna na formação, na graduação dos profissionais de saúde, sobre segurança do paciente, e de ausência de experiência profissional anterior à residência.…”
Section: Discussionunclassified
“…3,18 Research has suggested that the knowledge deficit of health professionals plays a prominent role in the management of PHD, a fact that implies medication errors on a regular basis. 3,15,19 In order to support this reflection, one study reported that the cognitive levels of a team consisting of doctors, nurses and pharmacists differed not only in terms of the profession but also in the degree of academic education. The research results indicated that the cognitive level associated with PHD should be improved, especially in the case of nurses, representing the final barrier between the drug administration and the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The research results indicated that the cognitive level associated with PHD should be improved, especially in the case of nurses, representing the final barrier between the drug administration and the patient. 19 In addition, the need to include the subject in the curricula of the courses that prepare these professionals should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…We selected the time for investigation with the convenient sampling method [20,21]. The project ''early identification of depression disorder in community elderly'' was beginning at August 2014.…”
Section: Participants and Study Designmentioning
confidence: 99%